Recombinant Human C1 Esterase Inhibitor for the Management of Adverse Events Related to Intravenous Immunoglobulin Infusion in Patients With Common Variable Immunodeficiency or Polyneuropathy: A Pilot Open-Label Study - Melamed, Isaac R.; Miranda, Holly; Heffron, Melinda; Harper, Joseph R. (Frontiers in Immunology, 2021)
It has been hypothesized that low levels of C1 esterase inhibitor (C1-INH), a key inhibitor of the complement pathway, may play a role in the occurrence of adverse events (AEs) associated with intravenous immunoglobulin (IVIG) therapy. This open-label pilot study evaluated C1-INH replacement, with recombinant human C1-INH (rhC1-INH), as a potential therapy for adults requiring IVIG and experiencing AEs. Patients received 2 rounds of IVIG infusion (pre-treatment phase [no rhC1-INH], 4–8 weeks) and then 3 rounds of 1 dose of intravenous rhC1-INH 50 U/kg (maximum, 4200 U) with subsequent IVIG infusion (treatment phase, 6–12 weeks). Nineteen adults completed the study; all had an autoimmune condition linked to common variable immunodeficiency (CVID) or polyneuropathy, and 57.9% had low baseline C1-INH levels. Mean ± SD total scores improved significantly with the Headache Impact Test (from 62.8 ± 6.2 at pre-treatment to 57.7 ± 9.1 after treatment; mean , –5.0; p = 0.02) and Modified Fatigue Impact Scale (from 59.3 ± 13.1 to 51.2 ± 15.4; mean , –8.1; p = 0.006). Significant improvements in the Migraine Disability Assessment were observed for 3 of 5 items (p ≤ 0.002). Mean ± SD C1-INH level increased from 26.8 ± 5.9 mg/dL after the second round of IVIG (pre-treatment) to 32.1 ± 7.8 mg/dL after the third rhC1-INH treatment; functional C1-INH levels increased from 115.8 ± 34.7% to 158.3 ± 46.8%. Future research is warranted to explore the benefit of C1-INH therapy for reduction of IVIG-related AEs, as well as the role of C1-INH in patients with CVID and autoimmune disease (ClinicalTrials.gov NCT03576469).